STATISTICAL METHODS FOR FORECASTING MUNICIPAL BUDGETS - Belostotskiy, Alexey (Revista Inclusiones, 2020)
The paper presents the study of the parameters of budget estimation in a municipal entity. The methodology is based on the approaches adopted for budget establishment in the city of Kursk, Russia, in the year 2016 and for the planning period of 2017–2018. These statistical methods are conductive to a more precise budgeting of revenues and expenditures, particularly so in the long term perspective